Coordinational council of the young scientists in Siberian State Medical University - L. V. Kapilevich (Бюллетень сибирской медицины, 2003)
The principals of creation and activity of Coordinational council of the young scientists in Siberian State Medical University are presented. The organizational structure and the main activities of Coordinational council of the young scientists in SSMU are shown.